Hog : proper pork recipes from the snout to the squeak - Turner, Richard H. (London, United Kingdom : Mitchell Beazley Publishers Limited, 2015)
The follow-up to the bestselling Pitt Cue Co. - The Cookbook, Hog is the ultimate pork cookbook, a masterpiece of meat cookery and an instant classic.
Prinal cuts: from wild boars to Berkshires -- Not-so-primal cuts: hogtopia -- Chopped, ground & mixed: feeding -- Sausages: breeding -- Cured: slaughter -- Snout to tail: butchery & buying -- Smoked: live fire cooking -- Basic recipes.
Includes index.
Keywords: COOKING -- PORK